Solid-state 2-methoxybenzoates of light trivalent lanthanides : SSSynthesis, characterization and thermal behaviour - Siqueira, A. B. [UNESP]; Bannach, Gilbert [UNESP]; Rodrigues, E. C. [UNESP]; Carvalho, C. T. [UNESP]; Ionashiro, Massao [UNESP] (Springer, 2008)
Solid-state LnL(3) compounds, where L is 2-metboxybenzoate and Ln is light trivalent lanthanides, have been synthesized. Thermogravimetry (TG), differential scanning calorimetty (DSC), X-ray powder diffractometry, infrared spectroscopy and elementary analysis were used to characterize and to study the thermal behaviour of these compounds. The results led to information on the composition, dehydration, thermal stability and thermal decomposition of the isolated compounds. on heating these complexes decompose in three (Ce, Pr) or five (La, Nd, Sm) steps with the formation of the respective oxide: CeO2, Pr6O11 and Ln(2)O(3) (Ln=La, Nd, Sm) as final residues. The theoretical and experimental spectroscopic study suggests predominantly the ionic bond between the ligand and metallic center.
Keywords: 2-methoxybenzoate; Light trivalent lanthanides; Thermal decomposition; Thermal stability; Trivalent lanthanides; Rare earth elements